A Panel data analysis on the impact of depopulation on refugee resettlement acceptance - KAGOYA, Georgina Joyce (KDI School, 2023)
The declining population growth rate in developed countries has stimulated debates and urban policy initiatives on how refugee resettlement in demographically challenged areas could counterbalance the negative consequences of a demographic decline while providing humanitarian support on the other hand. This study, therefore, sheds light on refugee resettlement in depopulating areas with a macro emphasis on refugee resettlement countries by checking whether depopulated countries are more likely to accept more refugees for resettlement. We utilize a panel fixed effect model to observe the causal relationship between refugee resettlement acceptance and population decline in all 43 countries that resettled refugees between 2000 and 2020. Our findings show a negative correlation between population growth rate and refugee resettlement acceptance and that a one percent decline in population growth rate is associated with a 0.19 percentage point increase in the number of refugees accepted for resettlement.
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Refugees--Social condition; Population